2011
DOI: 10.1007/s00508-011-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function-conduction impairment as reflected by the ECG in chronic aortic regurgitation

Abstract: The study was conducted to ascertain that the ECG assists in the assessment of systolic dysfunction in chronic aortic regurgitation. Five variables were reviewed in 146 adults without bundle branch block who underwent angiocardiography: total 12-lead QRS amplitude, QRS duration, maximum R peak time in I, V5 or V6, maximum R peak time relative to S peak time of the maximum S in V1, V2 or V3, and maximum T wave amplitude and polarity in I, V6 or aVF. In order to define which of them could differentiate left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Delayed time to ID is thought to represent conduction delay secondary to increases in left ventricular cavity size and increases in left ventricular end‐diastolic volume 31, 32. Similarly, abnormalities of left ventricular repolarization possibly detect structural abnormalities that predispose to HFrEF rather than HFpEF 29, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed time to ID is thought to represent conduction delay secondary to increases in left ventricular cavity size and increases in left ventricular end‐diastolic volume 31, 32. Similarly, abnormalities of left ventricular repolarization possibly detect structural abnormalities that predispose to HFrEF rather than HFpEF 29, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed time to ID is thought to represent conduction delay secondary to increases in left ventricular cavity size and increases in left ventricular end-diastolic volume. 31,32 Similarly, abnormalities of left ventricular repolarization possibly detect structural abnormalities that predispose to HFrEF rather than HFpEF. 29,33,34 This is supported by data that have shown that ST/T-wave abnormalities are not associated with diastolic dysfunction that would be expected in the development of HFpEF 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent examination of 146 adults with aortic insufficiency that found delayed ID to be highly predictive of a reduced ejection fraction (<50%) with a specificity of 89.1% (16). Additionally, delayed ID has been shown to suggest volume overload (e.g., increased left ventricular end-diastolic volume) in patients with chronic mitral regurgitation (17).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have identified ECG predictors of LV dysfunction as LV hypertrophy, left bundle branch block, prolongation of QRS duration, axial deviation, and R-peak delay, which was defined as the R-peak time in lead V5 or V6 exceeding the S-peak time in leads V1, V2, and V3. 27,28) The metabolic or structural changes associated with cardiomyopathic processes, such as cardiomyocyte hypertrophy, inflammation, and fibrosis, would result in ECG changes 29) . For example, prolongation of QRS duration and R-peak delays reflect ventricular depolarization abnormalities arising from conduction delays that are the result of increased LV end-diastolic volume.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prolongation of QRS duration and R-peak delays reflect ventricular depolarization abnormalities arising from conduction delays that are the result of increased LV end-diastolic volume. 29,30) These changes may have been detected by the developed model as changes in the QRS complex on ECG.…”
Section: Discussionmentioning
confidence: 99%